2013
DOI: 10.1152/ajprenal.00344.2012
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 11 insufficiency modulates kidney susceptibility to oxidative stress

Abstract: Lawson WE, Gow AJ, Harris RC, Dikov MM, Tchekneva EE. Aquaporin 11 insufficiency modulates kidney susceptibility to oxidative stress. Am J Physiol Renal Physiol 304: F1295-F1307, 2013. First published March 13, 2013 doi:10.1152/ajprenal.00344.2012.-Aquaporin 11 (AQP11) is a newly described member of the protein family of transport channels. AQP11 associates with the endoplasmic reticulum (ER) and is highly expressed in proximal tubular epithelial cells in the kidney. Previously, we identified and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
41
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 35 publications
0
41
1
Order By: Relevance
“…Accordingly, it is likely that AQPs other than AQP8 play complementary, tissue-and context-specific roles with regard to H 2 O 2 transport at the ER. One obvious candidate is AQP11, the subcellular localization of which is strongly shifted to the ER [45,46]. AQP11 loss-of-function causes destructive symptoms of ER stress, which mainly manifest in the proximal tubular epithelial cells of the kidney [45][46][47] but also in other organs such as the liver [48].…”
Section: Aquaporins Regulate the Permeability Of The Er Membrane To Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it is likely that AQPs other than AQP8 play complementary, tissue-and context-specific roles with regard to H 2 O 2 transport at the ER. One obvious candidate is AQP11, the subcellular localization of which is strongly shifted to the ER [45,46]. AQP11 loss-of-function causes destructive symptoms of ER stress, which mainly manifest in the proximal tubular epithelial cells of the kidney [45][46][47] but also in other organs such as the liver [48].…”
Section: Aquaporins Regulate the Permeability Of The Er Membrane To Hmentioning
confidence: 99%
“…One obvious candidate is AQP11, the subcellular localization of which is strongly shifted to the ER [45,46]. AQP11 loss-of-function causes destructive symptoms of ER stress, which mainly manifest in the proximal tubular epithelial cells of the kidney [45][46][47] but also in other organs such as the liver [48]. In addition to the tissue-specific expression level of ER AQPs, the H 2 O 2 permeability of the ER membrane is likely regulated by post-translational modifications.…”
Section: Aquaporins Regulate the Permeability Of The Er Membrane To Hmentioning
confidence: 99%
“…In the kidney, AQP11 is exclusively expressed in all PT segments and is regulated by glucose (2,26,37). Our and other studies have demonstrated that in mice, loss of AQP11 function in PTs leads to AKI (26,37) and that AQP11 insufficiency predisposes to hyperglycemia-induced renal dysfunction (2).…”
mentioning
confidence: 52%
“…We recently identified aquaporin (AQP)11 haploinsufficiency as a factor predisposing to hyperglycemia-induced nephropathy (2,36). AQPs, primarily water transport proteins, are characterized by the presence of two highly conserved Asn-Pro-Ala (NPA) motifs that, along with the surrounding sequences, are important for pore formation and its functioning (27,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation